Penerapan Model ELPSA dengan Bantuan Alat Peraga Geoboard untuk Meningkatkan Aktivitas dan Hasil Belajar Siswa pada Materi Bangun Datar - Wahyuddin, Wahyuddin (Jurnal Paedagogy, 2021)
The purpose of this research is to increase the activity and student learning outcomes on the flat shape material with the ELPSA model using geoboard props. This research method uses classroom action research. The subjects of this study were students of class VII A of SMP Negeri 2 Dompu, totaling 28 people. Data collection techniques using questionnaires, and tests. While the data analysis technique is descriptive quantitative and qualitative. The results of this study indicate that the application of the ELPSA model with the help of a geoboard tool on flat-shaped materials can improve student activities and learning outcomes. This is evidenced by the average increase in activity data of 55.36% in the first cycle, to 63.61% in the second cycle and increased to 74.49% in the third cycle. Data on the average increase in student learning outcomes from 55.06% in the first cycle, to 61.90% in the second cycle and increased to 67.41% in the third cycle. Based on the results of this study, teachers should always innovate to be able to motivate students' interest in learning and improve the quality of learning with varied learning models and appropriate teaching aids, so that student learning outcomes can be maximized.